Transformasi Sosial Dan Ekonomi Di Desa Batupute: Implikasi Pembangunan Industri Galangan Kapal - Alif, Nur; Haris, Andi; Arifin, Suryanto (Pusat Penelitian Kebijakan Pembangunan, Universitas Hasanuddin, 2024)
This study explores the socio-economic impacts of shipyard development in Batupute Village, Soppeng Riaja District, Barru Regency, Indonesia. The main objectives of this study are to understand community perceptions of shipyard development, identify the driving and inhibiting factors of the industry, and measure community expectations regarding the industry. The research method used is qualitative, with in-depth interviews and